The Effect of Aerobic and Core Exercises on Forced Vital Capacity - Çiçek Güner; Güllü Abdullah; Güllü Esin; Yamaner Faruk (Sciendo, 2018)
The aim of the study was to investigate the effect of aerobic and core strength exercises on forced vital capacity in sedentary women. A total of 40 healthy sedentary women (20 in an aerobic-step group and 20 in a core strength exercise group) with a mean age of 34.4±2.4 years participated voluntarily in this study. Two different exercises were applied to the women for 12 weeks, 4 days a week, at the intensity of 70% for 60 minutes. The women's resting heart rate (RHR), maximal oxygen consumption (VO2max), forced vital capacity (FVC), and forced air volume in the first second of forced expiration (FEV1) were measured before and after exercise. For statistical analysis, the Paired Samples-t test was used for intra-group evaluations, and the Independent Samples-t test was used for inter-group evaluations. After the exercise program, significant increases were found in the VO2max, FVC, and FEV1 values, while both groups experienced a decreased RHR (p<0.01). Since the aerobic and forced vital capacities of the sedentary women show a parallel increase as a result of the applied 12-week aerobic and core strength exercises, it can be said that the RHR, VO2maxmax, FEV, and FEV1 respiratory parameters also improved in a positive manner. For this reason, it may be advisable to apply both exercise types for the development of the aerobic and vital capacities of sedentary women.